Effect of Mg Doping on the Physical Properties of Fe2O3 Thin Films for Photocatalytic Devices - Rihab Ben Ayed; Mejda Ajili; Yolanda Piñeiro; Badriyah Alhalaili; José Rivas; Ruxandra Vidu; Salah Kouass; Najoua Kamoun Turki (Nanomaterials, 2022)
Undoped and Mg-doped (y = [Mg2+]/[Fe3+] = 1, 2, 3, and 4 at.%) Fe2O3 thin films were synthesized by a simple spray pyrolysis technique. The thin films were extensively characterized. X-ray diffraction (XRD) and energy-dispersive spectroscopy (EDS) analysis confirmed the successful insertion of Mg in the rhombohedral structure of Fe2O3. In addition, scanning electronic microscope (SEM) and confocal microscope (CM) images showed a homogenous texture of the film, which was free of defects. The rough surface of the film obtained by spray pyrolysis is an important feature for photocatalysis and gas sensor applications. The direct band gap of the doped Fe2O3 films obtained for [Mg2+]/[Fe3+] = 3 at.% was Edir = 2.20 eV, which recommends the Mg-doped iron oxide as an optical window or buffer layer in solar cell devices. The photodegradation performance of Mg-doped Fe2O3 was assessed by studying the removal of methylene blue (MB) under sunlight irradiation, with an effective removal efficiency of 90% within 180 min. The excellent photodegradation activity was attributed to the strong absorption of Mg-doped Fe2O3 in the UV and most of the visible light, and to the effective separation of photogenerated charge carriers.